Topographic landmarks in the evaluation of surgical time,morbidity and complications of tracheotomy - (:unkn) unknown (My University, 2018)
Objectives: This study aims to measure some topographic points and distances in the neck and investigate the effect of thesetopographic measurements on operative duration and complication rate.Patients and Methods: This observational prospective study included 65 patients (38 males, 27 females; mean age 66.1±12.1 years;range 23 to 85 years) who were performed conventional open tracheotomy Haydarpasa Numune Training and Research Hospitalbetween May 2012 and July 2014. Patients’ age, gender and weight (body mass index), duration of the procedure, and peri- andpostoperative complications were recorded. Mentum (M)-suprasternal notch (SN) and cricoid cartilage (CC)-SN distances weremeasured with a measuring tape. Neck circumference was measured at the levels of CC and cricothyroid membrane.Results: Operative duration was significantly longer in obese patients compared to normal weight and overweight patients (p=0.002;p=0.026; p<0.05). Perioperative complication rate was significantly lower in normal weight patients than overweight and obesepatients (p=0.004; p<0.01). There was a statistically significant inverse correlation between the CC-SN distance and operativeduration (r=-0.431; p=0.001; p<0.01). M-SN distance was significantly shorter in patients with perioperative complications (p=0.003,p<0.01).Conclusion: According to the study results, operative duration lengthens and perioperative complication rate increases as theweight increases and the neck length shortens.